Ecological and biogeographical drivers of freshwater green algae biodiversity: from local communities to large-scale species pools of desmids - Bestová, Helena; Munoz, François; Svoboda, Pavel; Škaloud, Pavel; Violle, Cyrille (Oecologia, 2018)
Dispersal limitation, niche-based processes as well as historical legacies shape microbial biodiversity, but their respective influences remain unknown for many groups of microbes. We analysed metacommunity structure and functional trait variation in 148 communities of desmids, freshwater green algae, distributed throughout Europe. We delineated biogeographic modules for both taxa and sites using bipartite network analysis given that the taxa of a module co-occurred more often than expected by chance in sites of the same module. The network analysis distinguished two main acidic and neutral habitats, reflecting environmental filtering, and within each habitat separated species pools with distinct geographic locations, representing a plausible influence of historical biogeography. The geographic differentiation was consistent with a hypothesis of glacial refugia on Atlantic coast. Distance decay in community composition in addition to environmental influence further suggested a role of dispersal limitation. Next, we quantified the variation in cell volume and surface-to-volume of taxa within and among communities, to examine morphological and physiological adaptations of desmids in varying environments. Communities from continental climate contained larger desmids. Conversely, we found a functional convergence of smaller, fast-growing, desmids in oceanic regions. Overall, our findings suggest that niche-based processes, dispersal limitation, and historical legacy together drive the distribution and structure of desmid communities. Combining trait- and network-based analyses can resolve long-lasting questions in microbial ecology and biogeography, and could be successfully used in macrobial ecology too.
Keywords: Functional trait; Desmidiales; Fresh Water; biodiverzita; Green algae; Europe; Evropa; Chlorophyta; sladká voda; Community assembly; Biogeography; Biodiversity; Bipartite network